2011
DOI: 10.1007/s00787-011-0214-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of psychiatric disorders in very young children in a Romanian pediatric setting

Abstract: Background A growing literature demonstrates that early clinical intervention can reduce risks of adverse psychosocial outcomes. A first step necessary for developing early intervention services is to know the prevalence of clinical disorders, especially in systems that are rebuilding, such as Romania, where the mental health system was dismantled under Ceaucescu. No epidemiologic studies have examined prevalence of psychiatric disorders in young children in Romania. Objective To determine the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 51 publications
(68 reference statements)
0
42
0
Order By: Relevance
“…In two studies (Velders et al 2011;Liu et al 2014a) low maternal education is related to increases in IEP, and one found no significant results on IEP (Gleason et al 2011). Only one study (Gleason et al 2011) assessed the effect of paternal low education, finding significant results indicating that when the fathers have a low education level, children tend to present more IEP. In the three studies mothers have a similar education distribution, and almost …”
Section: Parental Education and Agementioning
confidence: 90%
See 2 more Smart Citations
“…In two studies (Velders et al 2011;Liu et al 2014a) low maternal education is related to increases in IEP, and one found no significant results on IEP (Gleason et al 2011). Only one study (Gleason et al 2011) assessed the effect of paternal low education, finding significant results indicating that when the fathers have a low education level, children tend to present more IEP. In the three studies mothers have a similar education distribution, and almost …”
Section: Parental Education and Agementioning
confidence: 90%
“…In the review, four studies examined the role of SES on IEP. One study (Gleason et al 2011) indicated that low income increases IEP and two studies (Paterson et al 2013;Ciciolla et al 2014) reported that low SES increases EP. Only one study (Utendale and Hastings 2011) stated that SES does not have an influence on IEP.…”
Section: Demographic Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…In preschool children, attention seeking behavior, overbright emotional displays, and violation of physical and verbal boundaries of others also may occur (Zeanah and Gleason, in press). Indiscriminate behavior is rare in epidemiological studies (Egger et al, 2006;Gleason et al, 2011b), but it is one of the most common social abnormalities described in young children living in institutions (Zeanah et al, , 2005 and in those adopted out of institutions (Bruce et al, 2009;Chisholm, 1998;Rutter et al, 2010a). In addition to children in institutions, indiscriminate behavior has been identified in maltreated children in foster care Oosterman et al, 2007;Pears et al, 2010;Zeanah et al, 2004).…”
Section: Indiscriminate Behaviormentioning
confidence: 99%
“…In this context, Gleason et al [2] provide us with extremely interesting data coming from Romania. The authors assessed a sample of 1,003 children aged 18-60 months from two pediatric centers using state of the art instruments in a two-stage study.…”
mentioning
confidence: 99%